2023
DOI: 10.3390/diagnostics13122059
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Tumour Aggressiveness Based on Molecular Subtype and Race Measured by [18F]FDG PET Metabolic Metrics in Patients with Invasive Carcinoma of the Breast

Abstract: Breast cancer in women of African descent tends to be more aggressive with poorer prognosis. This is irrespective of the molecular subtype. [18F]FDG PET/CT metrics correlate with breast cancer aggressiveness based on molecular subtype. This study investigated the differences in [18F]FDG PET/CT metrics of locally advanced invasive ductal carcinoma (IDC) among different racial groups and molecular subtypes. Qualitative and semiquantitative readings of [18F]FDG PET/CT acquired in women with locally advanced IDC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Therefore, as a tumor becomes increasingly undifferentiated and aggressive, it results in elevated glucose utilization and increased uptake of the radioactive tracer 18 F-FDG. 19 , 20 Black patients with breast cancer have poorer prognosis and higher mortality. Abubakar et al 19 observed differences in 18 F-FDG PET–CT metabolic parameters of locally advanced invasive ductal carcinoma (IDC) among patients of different racial groups and molecular subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, as a tumor becomes increasingly undifferentiated and aggressive, it results in elevated glucose utilization and increased uptake of the radioactive tracer 18 F-FDG. 19 , 20 Black patients with breast cancer have poorer prognosis and higher mortality. Abubakar et al 19 observed differences in 18 F-FDG PET–CT metabolic parameters of locally advanced invasive ductal carcinoma (IDC) among patients of different racial groups and molecular subtypes.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 Black patients with breast cancer have poorer prognosis and higher mortality. Abubakar et al 19 observed differences in 18 F-FDG PET–CT metabolic parameters of locally advanced invasive ductal carcinoma (IDC) among patients of different racial groups and molecular subtypes. A notable increase in the SUV max , MTV, and TLG values of the primary tumor was observed in black patients when compared with patients of other ethnicities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations